Synthesis and Antileukemic Activity of New Fluorinated 5-Aza-9-deazapurines - Lim, F.; Kow, K.; Yeo, E.; Chow, S.; Dolzhenko, Anton (The Japan Institute of Heterocyclic Chemistry, 2016)
Novel fluorinated 4-benzylamino-7-phenylpyrazolo[1,5-a]- [1,3,5]triazin-2-amines were prepared using an efficient and practical approach. The chemoselectivity of condensation of pyrazolylguanidine and trichloroacetonitrile was found to be solvent-dependent and, when conducted in toluene, this reaction afforded 7-phenyl-4-trichloromethylpyrazolo[1,5-a]- [1,3,5]triazin-2-amine as the main product. This key intermediate underwent nucleophilic replacement of the trichloromethyl group with fluorinated benzylamines providing a series of the target compounds. Antiproliferative activity of the prepared compounds against Jurkat T cells was explored using MTS assay. Morphological changes observed in cells treated by the most potent compounds of this series, suggested that these compounds induced apoptosis in cells.